1985
DOI: 10.1136/bmj.290.6482.1633
|View full text |Cite
|
Sign up to set email alerts
|

Drugs prescribed for self poisoners.

Abstract: Of 230 adults admitted for self poisoning over two months, 153 (67%) had previously been taking a total of 309 prescribed drugs. Of these patients, 119 (78%) had been given psychotropic drugs (usually benzodiazepines), 81 (53%) obtained them on repeat prescription, and 47 (31%) had been prescribed multiple psychotropic drugs, often in seemingly illogical combinations. The use of these drugs increased progressively with age and most patients took the same drugs in overdosage as they had been prescribed. Psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…Las benzodiazepinas por su parte, se consolidan como el medicamento más frecuentemente encontrado en las intoxicaciones, aumentando su frecuencia a medida que pasan los años (Duce et al, 1998;Fernández et al, 2005;Burillo-Putze et al, 2006;Fernández et al, 2008) en detrimento de otros fármacos como los analgésicos o los antidepresivos tricíclicos. Actualmente la prescripción de psicofár-macos ha aumentado notablemente ya que son esenciales en el abordaje terapéutico de patologías cada día más frecuentes como la depresión y la ansiedad (Fernández et al, 2005), pero esta prescripción debería hacerse de forma muy controlada y prestando especial atención a los pacientes depresivos o con alto riesgo de depresión (Shah, Uren, Baker y Majeed, 2002), por riesgo a que éstos se intoxiquen con su propia medicación (Prescott y Highley, 1985). Por otra parte, en las intoxicaciones producidas por drogas de abuso, se ha visto como en la última década la cocaína ha adquirido un gran protagonismo (Burillo-Putze et al, 2006;Fernández et al, 2003;Fernández et al, 2008;García-Baró et al, 2005), mientras que el consumo de heroína ha disminuido sustancialmente.…”
Section: Discussionunclassified
“…Las benzodiazepinas por su parte, se consolidan como el medicamento más frecuentemente encontrado en las intoxicaciones, aumentando su frecuencia a medida que pasan los años (Duce et al, 1998;Fernández et al, 2005;Burillo-Putze et al, 2006;Fernández et al, 2008) en detrimento de otros fármacos como los analgésicos o los antidepresivos tricíclicos. Actualmente la prescripción de psicofár-macos ha aumentado notablemente ya que son esenciales en el abordaje terapéutico de patologías cada día más frecuentes como la depresión y la ansiedad (Fernández et al, 2005), pero esta prescripción debería hacerse de forma muy controlada y prestando especial atención a los pacientes depresivos o con alto riesgo de depresión (Shah, Uren, Baker y Majeed, 2002), por riesgo a que éstos se intoxiquen con su propia medicación (Prescott y Highley, 1985). Por otra parte, en las intoxicaciones producidas por drogas de abuso, se ha visto como en la última década la cocaína ha adquirido un gran protagonismo (Burillo-Putze et al, 2006;Fernández et al, 2003;Fernández et al, 2008;García-Baró et al, 2005), mientras que el consumo de heroína ha disminuido sustancialmente.…”
Section: Discussionunclassified
“…Various studies have shown that poisoning by medication is the most common method in deliberate self-harm (DSH) (Hawton & Fagg, 1992), and psychotropics, particularly benzo diazepines one of the most frequently used drug (Prescott & Highley, 1985). Recently, high rates and increasingly frequent self-poisoning with analgesics, especially paracetamol have been reported (Hawton & Fagg, 1992).…”
mentioning
confidence: 99%
“…Recently, high rates and increasingly frequent self-poisoning with analgesics, especially paracetamol have been reported (Hawton & Fagg, 1992). Less than half the patients overdosing with medications have been found to use one drug only, whereas 20-37% used 3 or more drugs (Prescott & Highley, 1985). The increased use of psychotropics has occurred in spite of the fact that in many countries prescription and dispensing of these drugs is strictly controlled.…”
mentioning
confidence: 99%
“…In addition, chloroquine has attained a reputation among the public as a mode of suicide and is relatively cheap and sold in supermarkets in Zimbabwe, whereas more traditional agents and non-prescription drugs in developed countries, e.g. paracetamol, 14,15 are expensive and sold in pharmacies. Although there was a statistically significant difference in median age between the chloroquine and other drugs groups (22 vs 20 years), this is unlikely to be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%